PENGARUH MEDIA PAPAN FLANEL PINTAR TERHADAP KEMAMPUAN MENGENAL HURUF PADA ANAK USIA 4-5 TAHUN DI TK AL-KAUSAR KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Sopia Julia Monika; Zulkifli N '; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the result of field observations on children’s ability to identify alphabet have not increased optimally. In that case, flannel board media utilization appliance is necessary to do. This research intend to discover the influence of smart flannel board utilization on 4-5 years old children at Al-Kausar Kindergarten in Tanah Putih district of the Rokan Hilir regency. The type this research is experiment with one group pretest post design 20 proteges was being used as samples for this research. As for the techniques that were used in this research was observation and documentation data analysis technique requires t-test check with spss 16.0 program applied. From the data analysis result we obtained tcount =35,512 and Sig = 0,000 with ttable 1,729 because tcount > ttabel with extent Sig < 0,05 in that case Ho means rejected and Ha means accepted which mean there is a very significant differencies of alphabet identifying ability between before and after applying smart flannel board utilization most of the influence smart flannel board utilization towards the alphabet identifying ability of 4-5 years old children at Al-Kausar Kindergarten in Tanah Putih district of Rokan Hilir Regency is about 46,3 %.